Pengaruh Pembiayaan Mudharabah Dan Pembiayaan Musyarakah Terhadap Profitabilitas (Roa) Pada Bank Syariah Indonesia Periode 2017-2021 - Meyliani Anggie S; Wirman Wirman (Peneliti.net, 2023)
Muslims follow sharia guidelines by behaving in an equivalent way in life. The economy in Indonesia is mostly engaged in the banking sector, almost all financial activities are related to banking in order to assist business actors when managing their finances to analyze the effect of mudharabah financing and musyarakah financing on profitability (ROA) at Indonesian Sharia Banks is the purpose of this study. The method required by the author is to use a quantitative descriptive method and the population is quarterly financial report data by Bank Syariah Indonesia for a period of five years during the 2017-2021 period. The results of the research examined by the authors show that: (1) partially, mudharabah financing has a negative and significant effect on the profitability of Return On Assets (ROA) at Bank Syariah Indonesia in the 2017-2021 period. The recognition is guaranteed on a sig. 0.000 < 0.05 and t count = -6.196 < t table = 2.110. (2) musyarakah financing has a significant positive effect on the profitability of Return On Assets (ROA) at Bank Syariah Indonesia with a nominal sig. 0.003 < α 0.05 and t count = 3.464 > t table = 2.110. (3) simultaneously, mudharabah financing and musyarakah financing have a significant influence on the profitability of Return on Assets (ROA) at Bank Syariah Indonesia for the 2017-2021 period. this is evident in the nominal sig. 0.000 < α 0.05 and f count = 45.169 > f table 3.55.